2015
DOI: 10.1257/pol.20140068
|View full text |Cite
|
Sign up to set email alerts
|

Trade and Investment under Policy Uncertainty: Theory and Firm Evidence

Abstract: Using a dynamic, heterogeneous firms model with sunk costs of exporting we show that: (i) investment and entry into export markets is reduced when trade policy is uncertain and (ii) credible preferential trade agreements (PTAs) increase trade even if applied trade barriers are currently low. We structurally estimate the effect of policy uncertainty on firm entry following Portugal's accession to the European Community in 1986 and find that (i) the trade policy reform accounted for a large fraction of the obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
267
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(278 citation statements)
references
References 30 publications
10
267
0
1
Order By: Relevance
“…6 For example, Colombo (2013) finds that a one standard deviation shock to the US economic policy uncertainty index leads to a statistically significant fall in European industrial production and prices. Handley and Limao (2012) find that trade policy uncertainty delays firm entry, and Gulen and Ion (2015) find negative responses of corporate investment to the EPU index. Gunnemann (2014) develops a policy uncertainty index, which relates to the Baker et al (2016) EPU index, and is based on over 60 million newspaper articles.…”
mentioning
confidence: 96%
“…6 For example, Colombo (2013) finds that a one standard deviation shock to the US economic policy uncertainty index leads to a statistically significant fall in European industrial production and prices. Handley and Limao (2012) find that trade policy uncertainty delays firm entry, and Gulen and Ion (2015) find negative responses of corporate investment to the EPU index. Gunnemann (2014) develops a policy uncertainty index, which relates to the Baker et al (2016) EPU index, and is based on over 60 million newspaper articles.…”
mentioning
confidence: 96%
“…We assume that the domestic firm incurs a fixed cost of K when starting the export, followed by variable costs of ( ) cx t η when producing ( ) x t units in period t, where c and η are parameters that satisfy c > 0 and η > 1. Here, entry costs cover the expenses of setting up a distribution network, on-site visits or agency costs and so on as in Handley (2014) [3] and Handley and Limao (2015) [4]. We also assume that the domestic firm optimizes the start time of the export, t * , as well as the amount of the export in each period.…”
Section: Basic Modelmentioning
confidence: 99%
“…), have entered a new stage since Handley (2014) [3], Handley and Limao (2015) [4] etc. raised the problem of optimal start time of export to show successfully that uncertain trade policy delays exporters' entry into new markets, by making use of optimal stopping theory that has been used to develop strategies on timing in a stochastic economy since McDonald and Siegel (1986) [5] demonstrated the value of waiting, followed by Dixit (1989) [6], Farzin, Huisman and Kort (1988) [7] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Second, TTBs are unlikely to provide incentives for firm entry since the WTO mandates that AD measures expire in five years with a (costly) possibility of extension, hence we can view TTBs as providing 5+ years of protection with duration uncertainty. In fact, recent literature has shown that trade policy uncertainty significantly deters trade and trade-induced structural change (see Handley (2014), Handley and Limao (2015), and Pierce and Schott (2016)). Lastly, TTBs are most often applied in declining industries which should discourage firm entry in the first place, especially if entry costs are large.…”
Section: Basic Environmentmentioning
confidence: 99%